Faktor Pendukung dan Penghambat Lembaga Pengelolaan Hutan Nagari (LPHN) dalam Produksi Minyak Kayu Putih di Nagari Tanjung Bonai Aur Kecamatan Sumpur Kudus Kabupaten Sijunjung - Andika, Septria; Eriyanti, Fitri (Lembaga Yasin AlSys, 2025)
This study is motivated by the strategic role of the Lembaga Pengelolaan Hutan Nagari (LPHN) Tanjung Bonai Aur in producing eucalyptus oil as a community economic resource and a means of environmental conservation. However, its implementation faces several challenges, including limited capital, unscheduled harvesting, and inconsistent distillation quality. The objective of this research is to analyze the strategies employed by LPHN in eucalyptus oil production and to identify the supporting and inhibiting factors affecting the success of these strategies. A descriptive qualitative method with a case study approach was used. Data were collected through field observations, interviews with LPHN management, business group members, and institutional partners, as well as documentation related to cultivation, distillation, packaging, and marketing processes. The analysis was conducted following the stages of strategy planning, implementation, and evaluation based on the framework of Robins and Coulter, and the analysis of supporting and inhibiting factors referred to the models of Hariyoko and Wibowo. The results show that LPHN's strategy is supported by synergy with local government, assistance from partner institutions, and strong internal motivation among members. However, key obstacles include limited business capital, lack of specific regulations, unstructured harvesting schedules, inconsistent distillation quality, unappealing packaging, and limited promotion and product legalization. Strategic evaluation highlights the need for strengthening partnerships, enhancing technological innovation, establishing structured harvesting plans, and implementing more systematic marketing and product legalization strategies. The study concludes that an integrated approach to managing eucalyptus oil production based on hutan nagari is essential for improving productivity, quality, and business sustainability.